Contraception masculine et querelles de genre - Oudshoorn, Nelly; Akrich, Madeleine; Le Doaré, Hélène (Cahiers du Genre, 1999)
Depuis la seconde guerre mondiale, treize nouveaux contraceptifs féminins ont été émis au point alors que les contraceptifs masculins sont à peu près inchangés depuis quatre cents ans. La responsabilité contraceptive, avec les risques qui en découlent pour la santé, est donc attribuée principalement aux femmes. Cet article se propose d’analyser le rôle de différents acteurs dans la réécriture éventuelle des rapports de genre autour de la contraception. Nous nous concentrerons sur le cas des nouvelles techniques contraceptives, surtout masculines, et la manière dont leurs utilisateurs sont définis. Alors que la plupart des travaux en sociologie des techniques insistent sur le rôle de l’innovation dans cette définition de l’utilisateur, nous montrerons qu’aux côtés des scientifiques, les féministes et les journalistes ont joué un rôle important dans la configuration des utilisateurs potentiels de ces techniques contraceptives : ils ont construit une grande variété de représentations de la masculinité et des utilisateurs hommes. Ces représentations sont utilisées soit pour montrer qu’il n’y a pas d’obstacle culturel à l’acceptabilité de ces techniques, soit à l’inverse, pour en dénoncer le caractère utopique.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; asie; cours; discipline; discours dominant; europe; hétérosexisme; inégalités; justice reproductive; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Re-orienting western feminisms: Women's diversity in a postcolonial world - Bulbeck, Chilla (Cambridge University Press, 1997)
The agenda of contemporary western feminism focuses on equal participation in work and education, reproductive rights, and sexual freedom. But what does feminism mean to the women of rural India who work someone else's fields, young Thai girls in the sex industry in Bangkok, or Filipino maids working for wealthy women in Hong Kong? In this 1998 book, Chilla Bulbeck presents a bold challenge to the hegemony of white, western feminism in this incisive and wide-ranging exploration of the lived experiences of 'women of colour'. She examines debates on human rights, family relationships, sexuality, and notions of the individual and community to show how their meanings and significance in different parts of the world contest the issues which preoccupy contemporary Anglophone feminists. She then turns the focus back on Anglo culture to illustrate how the theories and politics of western feminism are viewed by non-western women.
https://www-cambridge-org.proxy.bibliotheques.uqam.ca/core/books/reorienting-western-feminisms/95C497BE2E45B0F50C047DE198134677
Keywords: approches et analyses; asie; cours; discipline; fem1000; féminisme postcolonial; inde; intersectionnalité; militance; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques

L’éducation des enfants dans Le Chrysanthème et le sabre - Benedict, Ruth Fulton; Mécréant, Lise (Le Chrysanthème et le sabre, 1995)
Cet essai, écrit à distance, sur commande de l'Office of War Information, par une femme qui n'était jamais allée au Japon et en ignorait la langue, pour servir de manuel aux forces d'occupation américaines, réussit la gageure de demeurer, de l'avis général des Japonais, l'un des grands livres que l'on ait écrit sur eux. Des articles et des ouvrages ont, après lui, été publiés qui réfutent, complètent, approfondissent, réapprécient les interprétations de Ruth Benedict. Ces débats lui ont conféré la place d'une référence classique." Ce livre traite des habitudes qui paraissent naturelles et que nul ne songerait à remettre en cause au Japon. Il traite des situations où tout Japonais peut compter sur la courtoisie et de celles où il se sent honteux, des circonstances où il éprouve de l'embarras, de ce qu'il exige de lui-même." On y parle des règles de hiérarchie, de bienséance, de l'éducation des enfants, de morale sexuelle, de politique économique ...
Section: 355 p. ; 17 cm.
Keywords: 1900-1999; 1990-1999; approches et analyses; asie; cours; discipline; japon; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; thématiques

Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; lit3220; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppressions; thématiques; théologie; voiles islamiques

The rise of a gay and lesbian movement - Adam, Barry D. (Twayne, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis